2016
DOI: 10.1089/jpm.2015.0275
|View full text |Cite
|
Sign up to set email alerts
|

Patient Home Visits: Measuring Outcomes of a Community Model for Palliative Care Education

Abstract: PHV was perceived by participants as an effective way of providing interactive community education. A broad range of themes were addressed, and the participants reported high levels of learning in all domains of palliative care. There were no cases of patient or relative expression of distress as a result of PHV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Hospitals are not fit for managing patients' and their families' psychosocial problems. 29 Hospital-based oncologic treatment is limited to the hospital, and are not considered to be able to give the continued care for physical, psychosocial, emotional, and spiritual symptoms patients and their families are probably going through. 12 Those bariers made optimal PPC services are difficult to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals are not fit for managing patients' and their families' psychosocial problems. 29 Hospital-based oncologic treatment is limited to the hospital, and are not considered to be able to give the continued care for physical, psychosocial, emotional, and spiritual symptoms patients and their families are probably going through. 12 Those bariers made optimal PPC services are difficult to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Johnston et al [21] found that joint training and collaborative work between general physicians, district nurses, and specialist palliative care teams increased the knowledge amongst non-specialist services. Allo et al [22] had a similar result. The majority of participants in this study valued the patient home visit educational program that was very effective in upgrading knowledge and skills of community staff.…”
Section: Discussionmentioning
confidence: 65%
“…The community-based model implemented in Steinhauser's study ought to be incorporated into medical school curricula, so future doctors are well equipped for homebased care. 8 The community-based model will ensure medical students will familiarize oneself with prescribing, managing symptoms, and working in an end-of-life care MDT.…”
mentioning
confidence: 99%
“…Allo et al demonstrated that 95% of physicians agree that home visits were an effective teaching tool. 8 The lack of training in home-based palliative care is a major hurdle in the implementation of palliative care in the community. 8 This study states that for many, the preferred place of death is at home.…”
mentioning
confidence: 99%
See 1 more Smart Citation